2011
DOI: 10.1091/mbc.e10-10-0848
|View full text |Cite
|
Sign up to set email alerts
|

Mms1 and Mms22 stabilize the replisome during replication stress

Abstract: A mechanism is shown by which Mms1 and Mms22 promote DNA replication in the presence of replication stress: they stabilize the replisome at stalled replication forks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 76 publications
(156 reference statements)
2
26
1
Order By: Relevance
“…This hypothesis is clearly reinforced by our findings showing that RRM3 deletion leads to an increased enrichment of Mms22. In good agreement with the fact that Mms22 is recruited to chromatin in a DNA damage-, RTT109-, and RTT101-dependent manner (Dovey et al 2009; Ben-Aroya et al 2010;Vaisica et al 2011) and, in the light of recent work showing that the Rtt101-Mms1-Mms22 complex binds H3K56ac-H4 preferentially over unmodified H3-H4 (Han et al 2013), we foresee that H3K56ac signals DNA damage and directly recruits the Rtt101-Mms1-Mms22 complex behind the fork to ubiquitylate H3K56 acetylated histones, Ctf4, and various substrates leading to an increased DNA accessibility at damage sites and improved DNA repair. Alternatively, Ctf4 could also recruit the Rtt101-Mms1 at the DNA damage fork through its interaction with Mms22, and its function at the replisome could be subsequently regulated by the complex.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This hypothesis is clearly reinforced by our findings showing that RRM3 deletion leads to an increased enrichment of Mms22. In good agreement with the fact that Mms22 is recruited to chromatin in a DNA damage-, RTT109-, and RTT101-dependent manner (Dovey et al 2009; Ben-Aroya et al 2010;Vaisica et al 2011) and, in the light of recent work showing that the Rtt101-Mms1-Mms22 complex binds H3K56ac-H4 preferentially over unmodified H3-H4 (Han et al 2013), we foresee that H3K56ac signals DNA damage and directly recruits the Rtt101-Mms1-Mms22 complex behind the fork to ubiquitylate H3K56 acetylated histones, Ctf4, and various substrates leading to an increased DNA accessibility at damage sites and improved DNA repair. Alternatively, Ctf4 could also recruit the Rtt101-Mms1 at the DNA damage fork through its interaction with Mms22, and its function at the replisome could be subsequently regulated by the complex.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, our data strongly suggest that this effect is dependent upon an interaction between Ctf4 and Mms22. Similarly to ctf4D, deletion of MRC1 induces uncoupling between helicase and polymerase (Tanaka et al 2009;Mimura et al 2010;Vaisica et al 2011). In accord with this notion, we found that the replication function of MRC1 is also strongly deleterious for cells experiencing constitutive replicative damages in the absence of a functional H3K56ac pathway.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Fork stabilization could therefore be a conserved feature of DNA-strand-exchange enzymes. There are also multiple mechanisms to stabilize blocked replication forks in eukaryotes that do not require recombination enzymes (Lopes et al 2001;Tercero and Diffley 2001;Katou et al 2003;Szyjka et al 2005;Tittel-Elmer et al 2009;Vaisica et al 2011). Perhaps the increased numbers of forks in eukaryotes demands a reduced probability of individual blocked fork instability, requiring multiple stabilization mechanisms.…”
Section: Fork Stabilitymentioning
confidence: 99%